Event history and survival analysis - Allison, Paul David; Allison, Paul David (Los Angeles SAGE, 2014)
Social scientists are interested in events and their causes. Although even histories are ideal for studying the causes of events, they typically possess two features--censoring and time-varying explanatory variables--that create major problems for standard statistical procedures. Several innovative approaches have been developed to accommodate these two peculiarities of event history data. This volume surveys these methods, concentrating on the approaches that are most useful to the social sciences. In particular, Paul D. Allison focuses on regression methods in which the occurrence of events is dependent on one or more explanatory variables. He gives attention to the statistical models that form the basis of event history analysis, and also to practical concerns such as data management, cost, and useful computer software.--From publisher's description.
Introduction -- Discrete-time methods -- Parametric methods for continuous-time data -- Cox regression -- Multiple kinds of events -- Repeated events -- Conclusion.
First published in 1984 under the title: Event history analysis.
Includes bibliographical references (pages 85-87) and index.
Keywords: Event history analysis